2020
DOI: 10.1101/2020.06.27.174136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FMRP activates the translation of large autism/intellectual disability proteins and stimulates N-end rule E3 ligase Poe/UBR4 production within puromycin-sensitive RNP particles

Abstract: Mutations in Fmr1 are the leading heritable cause of intellectual disability and autism spectrum disorder. We previously found that Fmr1 acts as a ~2-fold activator of translation of large proteins in Drosophila oocytes, in contrast to its proposed role as a repressor of translation elongation. Here, we show that genes associated with autism spectrum disorders tend to be dosage-sensitive and encode proteins that are larger than average. Reanalysis of Fmr1 KO mouse cortex ribosome profiling data demonstrates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Earlier work has suggested that the coding sequence (CDS) length of an mRNA is associated with alterations in ribosome association in FXS. 47 50 To examine whether the CDS length of an mRNA dictates its ribosome association in dSPNs of FXS model mice, we ordered all mRNAs ascendingly by their CDS lengths, divided them into six color-coded bins, and evaluated their log2-fold changes (LFCs) against their FDR-adjusted p values. Consistent with the prior observations, mRNAs with the longest CDSs were enriched in genes with significantly reduced ribosome association in dSPNs of mice lacking FMRP, while those with the shortest CDSs were enriched in genes with significantly increased ribosome association ( Figure S4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has suggested that the coding sequence (CDS) length of an mRNA is associated with alterations in ribosome association in FXS. 47 50 To examine whether the CDS length of an mRNA dictates its ribosome association in dSPNs of FXS model mice, we ordered all mRNAs ascendingly by their CDS lengths, divided them into six color-coded bins, and evaluated their log2-fold changes (LFCs) against their FDR-adjusted p values. Consistent with the prior observations, mRNAs with the longest CDSs were enriched in genes with significantly reduced ribosome association in dSPNs of mice lacking FMRP, while those with the shortest CDSs were enriched in genes with significantly increased ribosome association ( Figure S4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has suggested that the coding sequence (CDS) length of an mRNA is associated with alterations in ribosome association in FXS 31,[45][46][47] . To examine whether the CDS length of an mRNA dictates its ribosome association in dSPNs of FXS model mice, we ordered all mRNAs ascendingly by their CDS lengths, divided them into six color-coded bins, and evaluated their log2-fold changes against their FDR-adjusted p-values.…”
Section: Trap-seq Of Drd1-spns Reveals a Coherent Reduction In Rgs4mentioning
confidence: 99%